Whether to kill : the cognitive maps of violent and nonviolent individuals - Dornschneider, Stephanie (University of Pennsylvania Press, 2016)
Whether to Kill takes a new approach to understanding terrorism. By taking first-person accounts of those involved in both violent and nonviolent action against the state, then analyzing that data via cognitive mapping, Stephanie Dornschneider has opened up new perspectives of what drives people to-or away from-the use of political violence.